Negotiations on market access within world trade organization - Jelisavac Sanja (Međunarodni Problemi, 2009)
In this paper the author examines GATT/WTO's actual contribution to lower tariffs and more open markets. The GATT has played a core role in the reduction of non-agricultural tariffs in developed countries, but some of the oft-quoted trade liberalization figures may be misleading. Developing countries for many decades prior to the Uruguay Round made little use of the GATT to reduce or bind their tariffs. Uruguay Round commitments have mostly extended the binding coverage, sometimes at levels far above the applied rates. It is also important to evaluate the effect of the GATT/WTO on border measures. Here again, the multilateral system can claim partial success. The author also examines GATT/WTO's contribution to world trade growth.